The Role of Accounting Internships in Preparing Students' Transition from School to Active Life - Nadia Albu; Daniela Artemisa Calu; Gina Raluca Guşe (Journal of Accounting and Management Information Systems (JAMIS), 2016)
The purpose of this paper is to investigate the extent to which accounting internships contribute to forming and developing students' competencies, practical abilities, professional and ethical values and to a more informed understanding of the accounting profession. We focus on the internship experience of a group of 159 second year students and utilize data from three sources. We survey students at the beginning and end of the internship and conduct content-analysis of students' essays describing the internship experience. We also survey tutors from the host organizations. Our research generally brings evidence from Romania to support the findings of most studies conducted in international research that internships have positive consequences on the development of students' skills and competencies. The main effects on the observed competencies include applying in practice the theoretical knowledge, technical competencies, as well as personal competencies (teamwork, communication). Internships facilitated a better understanding of accounting and the accounting profession. Moreover, we tackle the recent finding that Romanian students have a bias towards positive self-perception and methodologically address it with other techniques to collect data about students' internship. Therefore, we suggest for future research in this area that data triangulation is extremely important in discussing the consequences of internships for students.
Keywords: I21; 650; internships; transition from school to active life; accounting and audit career; competencies; accounting stereotype